2018
DOI: 10.1093/infdis/jiy449
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Human Echinococcosis via Exhaled Breath Analysis: A Promise for Rapid Diagnosis of Infectious Diseases Caused by Helminths

Abstract: Here we advocate a non-invasive, fast, easy-to-operate and non-expensive diagnostic tool for the diagnosis of human echinococcosis disease through exhaled breath analysis, suitable for early diagnosis and population screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The dynamic sensors' operation mode employed in this study, implemented by applying short voltage pulses to the sensors (10 s duration) followed by longer inactivity periods (90 s duration), allowed for analyzing the surface adsorption-desorption reaction kinetics that occur between the sensing material and the sensed VOCs. This operation mode provides more information than the static operation mode when the sensor is continuously operated at a constant voltage [32].…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic sensors' operation mode employed in this study, implemented by applying short voltage pulses to the sensors (10 s duration) followed by longer inactivity periods (90 s duration), allowed for analyzing the surface adsorption-desorption reaction kinetics that occur between the sensing material and the sensed VOCs. This operation mode provides more information than the static operation mode when the sensor is continuously operated at a constant voltage [32].…”
Section: Discussionmentioning
confidence: 99%
“…When sensors responses were individually analyzed for each sensor, the best discrimination accuracy was obtained by sensor S3. Alkane derivatives, such as methane, propane and iso-butane, detected by sensor S3, are recurrent oxidation products in the process of lipid peroxidation caused by highly unstable reactive oxygen species produced by the host as a result of immune responses against echinococcus infection [15,26,27]. Ethanol (detected by sensors S3 and S1) and ammonia (detected by sensors S3 and S2) are common breath metabolites.…”
Section: Sensors Characteristicsmentioning
confidence: 99%
“…In a very recent study, it was shown that a specifically-designed electronic nose system based on organically-functionalized metal nanoparticles trained for the detection of AE pattern in exhaled breath can discriminate with high accuracy between AE patients and healthy controls [15]. In that study, the sensors were operated in the DC mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new odor scanner developed in recent years, electronic nose had been widely used in medicine, food, beverage, cosmetics, and other fields. Welearegay et al [7] used electronic nose to diagnose the helminth infectious diseases based on the patience's exhalations. Li et al [8] used this technology to distinguish the Kiwifruit from different origins in China.…”
Section: Introductionmentioning
confidence: 99%